1990
DOI: 10.1148/radiology.174.2.2136958
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic changes associated with postmenopausal hormone replacement therapy: a longitudinal study.

Abstract: A retrospective study of radiologic findings from 50 postmenopausal women who underwent hormone replacement therapy was performed to determine the frequency and distribution of changes in the screen-film mammographic appearance of breast tissue between pretreatment and posttreatment mammography. Twelve (24%) of the women developed increased parenchymal density during a median follow-up of 18 months (range, 6-39 months). Mammographic changes included diffuse increase in density in seven (14%) of the women; incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0
4

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(65 citation statements)
references
References 0 publications
4
57
0
4
Order By: Relevance
“…This effect showed a statistically significant difference (p = 0.045) from the oestrogen-alone group. In another retrospective study by Stomper et al [19] 50 postmeno pausal women (median age 52 years, range 40-69 years) were treated with either oestrogens alone (n = 12) or a combination of oestrogens and progestagens (n ~ 38), for a median period of 18 months (range 6-39 months). Two oestrogen-alone users (1 7 % ) and 10 oestrogen/ progestagen users (26 % ) showed increased breast den sities, but this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect showed a statistically significant difference (p = 0.045) from the oestrogen-alone group. In another retrospective study by Stomper et al [19] 50 postmeno pausal women (median age 52 years, range 40-69 years) were treated with either oestrogens alone (n = 12) or a combination of oestrogens and progestagens (n ~ 38), for a median period of 18 months (range 6-39 months). Two oestrogen-alone users (1 7 % ) and 10 oestrogen/ progestagen users (26 % ) showed increased breast den sities, but this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…the evaluation of both an oestrogen therapy group and a com bination oestro gen/progestagen therapy group [18,19]; the median age and the median follow-up period of the populations in vestigated [18,19]; the percentage of women with an in crease in fibroglandular tissue after H R T [19]; and the statistically significant difference between the oestrogen group and the oestrogen/progestagen group [18], H ow ever, there are some differences also. In our hospitalbased study we evaluated 81 women, which is approxi mately two times more than the other two studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T he breast is a highly heterogeneous and dynamically complex organ whose characteristics depend on factors such as age, hormonal status, habitus, family and medical history, and genetics (1)(2)(3). Normal breast tissue changes considerably during development, pregnancy, and menopause, and throughout the menstrual cycle.…”
mentioning
confidence: 99%
“…Numerous studies have reported mammographic density changes in women who start combined estrogen and progestin therapy (EPT), most have been from the US (43)(44)(45)(46)(47)(48). Two placebo-controlled randomized trials from the US, the Postmenopausal Estrogen and Progestin Interventions (PEPI) trial (46,48), and the Women's Health Initiative (WHI) trial (49) found that women assigned to the EPT arm had on average a 5% and 6% increase in mammographic density respectively after 1 year, while there were only minor changes in the placebo group or the estrogen alone arm.…”
Section: Postmenopausal Hormone Usementioning
confidence: 99%